2017
DOI: 10.4103/ajns.ajns_67_14
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia

Abstract: Trigeminal neuralgia (TN) is a sudden, severe, brief, stabbing, and recurrent pain within one or more branches of the trigeminal nerve. Type 1 as intermittent and Type 2 as constant pain represent distinct clinical, pathological, and prognostic entities. Although multiple mechanism involving peripheral pathologies at root (compression or traction), and dysfunctions of brain stem, basal ganglion, and cortical pain modulatory mechanisms could have role, neurovascular conflict is the most accepted theory. Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 230 publications
(313 reference statements)
1
104
0
2
Order By: Relevance
“…The mechanism for this extreme predilection to develop HFS/TN is unclear. As in our kindred, sporadic cases of HFS and TN demonstrate advancing incidence with age and the onset age for sporadic HFS and TN is similar to that in our kindred . Sporadic HFS/TN is believed to be caused by compression of the cranial nerves by adjacent vasculature and this risk could be increased by nerve hypertrophy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The mechanism for this extreme predilection to develop HFS/TN is unclear. As in our kindred, sporadic cases of HFS and TN demonstrate advancing incidence with age and the onset age for sporadic HFS and TN is similar to that in our kindred . Sporadic HFS/TN is believed to be caused by compression of the cranial nerves by adjacent vasculature and this risk could be increased by nerve hypertrophy.…”
Section: Discussionsupporting
confidence: 83%
“…As in our kindred, sporadic cases of HFS and TN demonstrate advancing incidence with age and the onset age for sporadic HFS and TN is similar to that in our kindred. 32,33 Sporadic HFS/TN is believed to be caused by compression of the cranial nerves by adjacent vasculature 34,35 and this risk could be increased by nerve hypertrophy. Using neuromuscular ultrasound, we have previously shown that this family has hypertrophic nerves including the vagus nerve 36 and other MPZ mutations have been associated with cranial nerve thickening.…”
Section: Discussionmentioning
confidence: 99%
“…The attacks of pain occur more frequently and more severely with time [6,7] and may manifest with one or several symptoms such as intense, shooting, stabbing pain that is similar to electric shocks, intermittent twinges of mild pain,spasms of pain, episodes of cluster attacks. TN pain can be focused in a specific area or spread over a widespread area [7,8,9] . TN pain episodes can last from a few seconds to several minutes, usually unilaterally, or less frequently on both sides of the face.…”
Section: Introductionmentioning
confidence: 99%
“…The attacks of pain may go into remission and patients maybe symptomless for months or years [5,7] . Women are twice as likely to be affected with this condition as men and in both genders, it is more prevalent after the age of 40 years [1,3] , with a prevalence of 4.3 per 100,000 [8,10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation